Garch Modeling for Volatil Data: Air Pollution Standard Index in DKI Jakarta as A Parameter in Secure Smart City Development - Qomariasih, Nurul; Kabetta, Herman; Buana, I Komang Setia; Pramadi, Yogha Restu (Budapest International Research and Critics University, 2021)
The DKI Jakarta government has the Jakarta Kini Application (JAKI) which was developed by the Jakarta smart city management unit. There is a JakISPU feature that displays the air pollution standard index (ISPU) in real-time, but the ISPU forecast value is not presented to prevent the ISPU from worsening in the future. This study presents a model for the concentration value of the ISPU parameter which has high volatility. The model obtained is expected to be used for forecasting the ISPU concentration value in the next few days. The resulting model is the SO2 arch garch model, namely and arch garch. Model NO2 that is . The model formed is free from the assumption of heteroscedasticity.